Johan P. Olsen, Demokrati på svenska, Stockholm: Carlson Bokförlag, 1990,182 s.; Johan P. Olsen (red.), Svensk demokrati i forandring, Stockholm: Carlson Bokforlag, 1991, 261 s. - Hansen, Karin (Politica, 1992)
-